Meg at sea - Nicoll, Helen; Pienkowski, Jan. (New York : Puffin, 1973)
A witch and her cat are shipwrecked on a deserted island.
Keywords: Cats -- Fiction; Witches -- Fiction; Cats -- Fiction; Witches -- Fiction